2011
DOI: 10.1186/1472-6963-11-330
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contribution of prescribing in primary care by nurses and professionals allied to medicine: a systematic review of literature

Abstract: BackgroundSafe and timely access to effective and appropriate medication through primary care settings is a major concern for all countries addressing both acute and chronic disease burdens. Legislation for nurses and other professionals allied to medicine to prescribe exists in a minority of countries, with more considering introducing legislation. Although there is variation in the range of medicines permitted to be prescribed, questions remain as to the contribution prescribing by nurses and professionals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 48 publications
1
80
0
1
Order By: Relevance
“…Prescribing to patients was the exclusive role of doctors and dentists, until the introduction of non-medical prescribing (NMP) in some countries which allowed non-medical professionals including nurses and pharmacists to prescribe medicines [2,3]. A number of countries have legislated for NMP including the United States of America (USA), United Kingdom (UK), Australia, New Zealand, Canada, Sweden, Republic of Ireland, South Africa, Botswana, Kenya and Uganda [4]. Nurse prescribing is the most popular form of NMP.…”
Section: Introductionmentioning
confidence: 99%
“…Prescribing to patients was the exclusive role of doctors and dentists, until the introduction of non-medical prescribing (NMP) in some countries which allowed non-medical professionals including nurses and pharmacists to prescribe medicines [2,3]. A number of countries have legislated for NMP including the United States of America (USA), United Kingdom (UK), Australia, New Zealand, Canada, Sweden, Republic of Ireland, South Africa, Botswana, Kenya and Uganda [4]. Nurse prescribing is the most popular form of NMP.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, national studies of supplementary prescribing (Bissell et al, 2008) mental health nurse prescribing (Norman et al, 2010) and independent prescribing in Ireland (Naughton et al, 2013) all showed largely positive findings, and so helped build support and confidence for nurse prescribing in the UK. Studies demonstrate that the prescription of medication by nurses is safe and competent, has led to better access and quality of care for patients, improvements in the abilities and experience of nurses, increased professional recognition, the legitimation of responsible autonomous practice and enabled better team working between the various healthcare professionals (Latter et al, 2012;Kroezen et al, 2011;Bhanbhro et al, 2011). Kroezen et al (2011) state that patient support and grassroots legislative constituency are crucial in battles over prescribing rights and these UK national studies all consistently reported patient support for nurse prescribing.…”
mentioning
confidence: 99%
“…72 There has also been research into NMP in Australia, Canada, and the USA. 62,73,74 There is a considerable lack of research on NMP in NZ compared with other countries. 72 The establishment of a collaborative research network in NZ could address this issue.…”
Section: Areas For Further Researchmentioning
confidence: 99%